Social capital in a regional inter-hospital network among trauma centers (trauma network): results of a qualitative study in Germany - Julika Loss; Johannes Weigl; Antonio Ernstberger; Michael Nerlich; Michael Koller; Janina Curbach (BMC, 2018)
Abstract Background As inter-hospital alliances have become increasingly popular in the healthcare sector, it is important to understand the challenges and benefits that the interaction between representatives of different hospitals entail. A prominent example of inter-hospital alliances are certified 'trauma networks', which consist of 5-30 trauma departments in a given region. Trauma networks are designed to improve trauma care by providing a coordinated response to injury, and have developed across the USA and multiple European countries since the 1960s. Their members need to interact regularly, e.g. develop joint protocols for patient transfer, or discuss patient safety. Social capital is a concept focusing on the development and benefits of relations and interactions within a network. The aim of our study was to explore how social capital is generated and used in a regional German trauma network. Methods In this qualitative study, we performed semi-standardized face-to-face interviews with 23 senior trauma surgeons (2013-14). They were the official representatives of 23 out of 26 member hospitals of the Trauma Network Eastern Bavaria. The interviews covered the structure and functioning of the network, climate and reciprocity within the network, the development of social identity, and different resources and benefits derived from the network (e.g. facilitation of interactions, advocacy, work satisfaction). Transcripts were coded using thematic content analysis. Results According to the interviews, the studied trauma network became a group of surgeons with substantial bonding social capital. The surgeons perceived that the network's culture of interaction was flat, and they identified with the network due to a climate of mutual respect. They felt that the inclusive leadership helped establish a norm of reciprocity. Among the interviewed surgeons, the gain of technical information was seen as less important than the exchange of information on political aspects. The perceived resources derived from this social capital were smoother interactions, a higher medical credibility, and joint advocacy securing certain privileges. Conclusion Apart from addressing quality of care, a trauma network may, by way of strengthening social capital among its members, serve as a valuable resource for the participating surgeons. Some member hospitals could exploit the social capital for strategic benefits.